The quirks of digital culture - Beer, David (Emerald Publishing Limited, 2019)
The culture we consume is increasingly delivered to us via various digital on-demand platforms. The last decade has seen platforms like Facebook, Amazon, Netflix, Spotify, Google and the like become massive players in shaping cultural consumption. But how can we understand culture once it moves on to big tech platforms? How can we make sense of the changes this brings to our lives? These platforms have the power to shape our cultural landscape and to use data, algorithms and other technological means to shape our experiences, from what we remember through to what we know and even the speed and accessibility of culture. This book asks how can we understand the chaos and messiness of on-demand culture? Beer suggests that we focus on the quirks and use these as openings to see inside patterns and dynamics of these new cultural formations. By exploring the strange quirks that typify our new on-demand culture, this book seeks to answer these questions. The Quirks of Digital Culture is a guide to understanding the complex and unsettling cultural present, whilst also casting an eye on how our consumption and cultural experiences may unfold in what seems like an unpredictable future.
Includes index.
Keywords: Internet -- Social aspects.; Internet -- Technological innovations.; Mass media -- Social aspects.; Culture.; Computers, Internet -- General.; Internet: general works.; elektronické knihy; electronic books